2017
DOI: 10.1371/journal.pone.0173099
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study to evaluate the performance of five statistical monitoring methods when applied to different time-series components in the context of control programs for endemic diseases

Abstract: Disease monitoring and surveillance play a crucial role in control and eradication programs, as it is important to track implemented strategies in order to reduce and/or eliminate a specific disease. The objectives of this study were to assess the performance of different statistical monitoring methods for endemic disease control program scenarios, and to explore what impact of variation (noise) in the data had on the performance of these monitoring methods. We simulated 16 different scenarios of changes in we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Two Bayesian forecast models, a DLM and a DGLM, both with a linear trend, as described by [6] were used to model the different time-series. The aim of these models is to estimate the underlying true value combining the observed data (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two Bayesian forecast models, a DLM and a DGLM, both with a linear trend, as described by [6] were used to model the different time-series. The aim of these models is to estimate the underlying true value combining the observed data (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…However, these methods might result in false alarms when applied to laboratory diagnostic data characterized by random noise and, as a consequence, with the costs of investigation of these alarms as well as a lower trust on the monitoring system. One alternative approach could be to monitor the trend of the underlying level of the time series, which can be positive or negative depending on whether the time series exhibits an increasing or decreasing pattern [5, 6]. This is particularly useful for monitoring temporal changes in trends laboratory diagnostic results collected as part of voluntary disease monitoring programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A univariate dynamic linear model (DLM) with a local linear trend component, as described in detail by West and Harrison (11) and applied in previous studies (12)(13)(14)(15), was used to model data at the herd level. A previous study showed that Bayesian forecasting methods adapt faster to changes in the data, compared to the deterministic Holt's linear trend methods for monitoring trends of time-series (14).…”
Section: Modeling and Parameterizationmentioning
confidence: 99%
“…The growth was extracted from the θ vector of the model for each time step t for every single herd. The variance of the trend parameter, calculated from the variance-covariance matrix for the posterior distribution, as previously described (12), was used to calculate 95% credible intervals (CI). The percentage of herds with a negative growth or a significant decline (based on 95%) below zero, CI in the antimicrobial consumption for a given month i were both calculated as:…”
Section: Monitoring Changes In Data Streamsmentioning
confidence: 99%